Perceptual processes and multisensoriality: Understanding multimodal art from neuroscientific concepts - Leote, Rosangella [UNESP] (My University, 2018)
Perception seems to be an overly discussed subject in theories of Art, giving us the impression that there is nothing new to add. So much research and so many conceptions have been developed on the subject. Nevertheless, many holes can be perceived in these theories with regard to the mental process that operates in the perception phenomena. We have chosen to look to neuroscience for possible answers to these holes. In this paper, based on the knowledge of Vilayanur S. Ramachandran and António Damásio, among others, we focus on that which we are emphasizing as perceptual processes. We will restrict ourselves herein to the perceptual processes of a multisensory nature that take place in the perceivers' relationship with the artworks, which contain multimodal stimuli, promoted by physical and digital interfaces of an assistive nature. Said perceivers, however, are both people with severe motor and vocal disabilities as well as those without these restrictions.